Case-control association between CCT-associated variants and keratoconus in a Saudi Arabian population - Abu-Amero, Khaled K. (J Negat Results Biomed, 2015)
BACKGROUND: Keratoconus (KC) is the most common primary ectatic disease of the cornea and a major indication for corneal transplant. To date, limited KC-associated-risk loci have been identified. Association has recently been suggested between KC and 8 single nucleotide polymorphisms (SNPs) in the genomic regions of FNDC3B, COL4A3, MPDZ-NF1B, RXRA-COL5A1, LCN12-PTGDS, FOXO1, and BANP-ZNF469. These SNPs are associated with central corneal thickness (CCT), a known risk factor to KC. We are questioning whether these SNPs are significantly associated with KC in a Saudi Arabian population. The study included 108 unrelated KC cases and 300 controls. Patients were diagnosed with KC according to the Schimpff-flow based elevation map of the cornea. DNA genotyping was done using probe-based allelic discrimination TaqMan assays. Allele frequencies were compared between the cases and controls. RESULTS: All SNPs were successfully genotyped with high efficiency (>95 %). The SNPs had no significant deviation in cases or controls from Hardy-Weinberg Equilibrium (HWE, p value > 0.05). None of the selected SNPs were significantly associated with KC in the Saudi Arabian population. However, we replicated the same trend of minor allele frequency (MAF) between cases and controls reported by a recent GWAS regarding the 5 SNPs rs4894535 (FNDC3B, chr3: 171995605), rs1536482 (RXRA-COL5A1, chr9: 137440528), rs7044529 (COL5A1, chr9: 137568051), rs11145951 (LCN12-PTGDS, chr9: 139860264), and rs2721051 (FOXO1, chr13: 41110884). CONCLUSIONS: This is the first study investigating the association of these SNPs with KC in a population from Saudi Arabia. We replicated the same trend of MAF alteration of the association between the SNPs rs4894535 (FNDC3B, chr3: 171995605), rs7044529 (COL5A1, chr9: 137568051), rs11145951 (LCN12-PTGDS, chr9: 139860264) and rs2721051 (FOXO1, chr13: 41110884) and KC-risk as reported by a recently published GWAS. Consistently replicated population-based studies are necessary to identify and/or confirm genetic susceptibility for certain diseases. We acknowledge that the lack of significance in our study is due to our small sample size and insufficient statistical power; however our data still add to the body of evidence of potential KC-candidate SNPs. This report aims at supporting the possible association between CCT-associated SNPs and KC susceptibility.